Influence of temperature reaction for the CdSe-TiO2 nanotube thin film formation via chemical bath deposition in improving the photoelectrochemical activity - Lai C.W.; Samsudin N.A.; Low F.W.; Abd Samad N.A.; Lau K.S.; Chou P.M.; Tiong S.K.; Amin N. (MDPI AG, 2023)
Deposition; Electrochemistry; II-VI semiconductors; Morphology; Nanotubes; Optical properties; Oxide minerals; Photocurrents; Selenium compounds; Surface morphology; Thin films; Titanium dioxide; Chemical compositions; Chemical-bath deposition; Deposition temperatures; Low deposition temperature; Photoelectrochemical performance; Photoelectrochemicals; Thin film morphology; Titanium dioxides (TiO2); Cadmium compounds